Health-related quality of life in European women following myocardial infarction: A cross-sectional study. (1st August 2015) - Lidell, Evy; Höfer, Stefan; Saner, Hugo; Perk, Joep; Hildingh, Cathrine; Oldridge, Neil
Abstract: Background: Coronary heart disease is a major contributor to women's health problems. Design: Self-perceived social support, well-being and health-related quality of life (HRQL) were documented in the cross-sectional HeartQoL survey of European women one and six months after a myocardial infarction. Methods: European women were recruited in 18 European countries and grouped into four geographical regions (Southern Europe, Northern Europe, Western Europe and Eastern Europe). Continuous socio-demographic variables and categorical variables were compared by age and region with ANOVA and χ 2, respectively; multiple regression models were used to identify predictors of social support, well-being and HRQL. Results: Women living in the Eastern European region rated social support, well-being and HRQL significantly lower than women in the other regions. Older women had lower physical HRQL scores than younger women. Eastern European women rated social support, well-being and HRQL significantly lower than women in the other regions. Prediction of the dependent variables (social support, well-being and HRQL) by socio-demographic factors varied by total group, in the older age group, and by region; body mass index and managerial responsibility were the most consistent significant predictors.